2024
DOI: 10.1039/d3cs00963g
|View full text |Cite
|
Sign up to set email alerts
|

Urea catalytic oxidation for energy and environmental applications

Xintong Gao,
Shuai Zhang,
Pengtang Wang
et al.

Abstract: This review evaluates state-of-the-art advances in electrocatalytic and photo(electro)catalytic urea oxidation from fundamentals and materials to energy and environmental applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 327 publications
(523 reference statements)
0
7
0
Order By: Relevance
“…22,23 It is worth noting that one urea molecule comprises an electron-donating amino group (−NH 2 ) and an electron-withdrawing carbonyl group (−C�O), which tends to adsorb onto distinct catalytic sites to generate crucial intermediates (CO* and NH*) upon breaking the C�O bond. 24,25 It plays a vital role in the electro-oxidation reaction of urea. Hence, it is imperative to design a rational electrocatalyst to promote the dissociation of urea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 It is worth noting that one urea molecule comprises an electron-donating amino group (−NH 2 ) and an electron-withdrawing carbonyl group (−C�O), which tends to adsorb onto distinct catalytic sites to generate crucial intermediates (CO* and NH*) upon breaking the C�O bond. 24,25 It plays a vital role in the electro-oxidation reaction of urea. Hence, it is imperative to design a rational electrocatalyst to promote the dissociation of urea.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing environmental concerns and global demand for sustainable energy, it is imperative to investigate alternative sources of eco-friendly and renewable energy as a substitute for conventional fossil fuels. Electrolysis of water has received significant attention owing to its potential to continuously produce hydrogen and replace fossil fuels through a sustainable process. However, the efficiency of water electrolysis is often hindered by the sluggish oxygen evolution reaction (OER), which is inhibited by the steps of O–O bond formation and O–H bond breaking with slow reaction kinetics. In recent years, oxidation reactions of organic molecules (such as urea, ethanol, and hydrazine) have been considered an alternative to OER owing to favorable thermodynamic potentials. The urea oxidation reaction (UOR) exhibits better thermodynamic favorability than OER, with a lower theoretical potential ( E = 0.37 V vs the reversible hydrogen electrode (RHE)) compared to that of OER ( E = 1.23 V vs RHE). However, the process of urea electro-oxidation still involves a complex six-electron-transfer step, which also imposes significant limitations on the reaction kinetics. , It is worth noting that one urea molecule comprises an electron-donating amino group (−NH 2 ) and an electron-withdrawing carbonyl group (–CO), which tends to adsorb onto distinct catalytic sites to generate crucial intermediates (CO* and NH*) upon breaking the CO bond. , It plays a vital role in the electro-oxidation reaction of urea. Hence, it is imperative to design a rational electrocatalyst to promote the dissociation of urea.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing carbon dioxide emissions is crucial for achieving sustainable development. , Hydrogen production by water electrolysis is an emerging and promising method. , However, oxygen evolution reaction (OER) has some inherent disadvantages, including slow kinetics, high theoretical potential (1.23 V vs RHE), and uneconomical products, which hinder the widespread adoption of this method. To overcome these limitations, researchers have been exploring the urea oxidation reaction (UOR) with a theoretical voltage of only 0.37 V vs RHE to break bottleneck. , Numerous studies have shown that UOR does not impede the generation of H 2 during water electrolysis. Furthermore, when UOR is applied to seawater electrolysis, it can prevent the competition of chlorine evolution reaction and broaden the potential selection range for the hydrogen evolution reaction (HER) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, urea is ubiquitous in life. UOR can decompose urea, purify sewage, and bring environmental benefits. , Therefore, the development of efficient UOR can contribute to a greener economy by enabling energy-saving hydrogen production and environmental purification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation